Tough, Long-Term, Water-Resistant, and Underwater Adhesion of Low-Molecular-Weight Supramolecular Adhesives - Li, Xing; Deng, Yan; Lai, Jinlei; Zhao, Gai; Dong, Shengyi (Journal of the American Chemical Society, 2020)
Modern functional adhesives have attracted considerable attention due to their reversible adhesion capacities and stimuli-responsive adhesion behavior. However, for modern functional adhesives, polymeric structures were highly necessary to realize adhesion behaviors. Supramolecular adhesives from low-molecular-weight monomers were rarely recognized. Compared with polymeric adhesive materials, it remains challenging for supramolecualr adhesive materials to realize tough adhesion on wet surfaces or even under water. In this study, a new supramolecular adhesive consisting of low-molecular-weight monomers was successfully designed and prepared. Strong and long-term adhesion performance was realized on various surfaces, with a maximum adhesion strength of 4.174 MPa. This supramolecular adhesive exhibits tough and stable adhesion properties in high-moisture and underwater environments (including seawater). Long-term underwater adhesion tests display the potential application of low-molecular-weight adhesive as a marine adhesive.